Use of Finite Difference Time Domain (FDTD) Technique to Calculate Poynting Vector in Free Space with Obstacles in Computational Domain - Farhat, Sedig S. (The Libyan Journal of Science, 2021)
In this paper, electromagnetic simulations in the two- and three-dimensions systems are performed by the finite difference time domain (FDTD) technique. The method can be applied for solving Maxwell’s curl equations numerically to calculate the Poynting vector distributions when placing the obstacles in the centre of a domain. Perfect electric conductor (PEC) structures of convenient shapes were constructed based on the geometric shape of the obstacle such as two parallel strips and triangle shapes in order to make a comparison between the simulations. The FDTD method will determine the values of the electric and magnetic field at any point in space and the grid is terminated with the first-order Gerrit Mur’s absorbing boundary condition (ABC) [1]. The boundary condition can be included in the calculations to absorb the waves when striking the boundaries. The ABC can affect the accuracy of the solutions as the calculations results demonstrate that good numerical performance of the FDTD obtained when utilizing the Mur’s ABC. In the provided examples, the achieved results indicate that very good radiation patterns were obtained when ABCs are implemented at all the edges. The results of FDTD simulations have shown that we have simulated the wave propagation in open domains.